Analisis Rasio Likuiditas Terhadap Kinerja Keuangan Pada PT. Bank Pembangunan Daerah Sumatera Utara - Paramita, Silvia; Sinaga, Fadli; Chairina, Chairina (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Banking plays an important role in the country’s economic development because banking is an institution that controls the country’s economy. Public trust continues to increase along with the improvement in the quality of services provided by banks. This study was conducted by looking at the bank’s ability to fulfill its obligations, namely in terms of financial performance, namely to determine the level of bank liquidity. This liquidity ratio measures the ability of a company or bank to pay its debts or short-term obligations. The research subjects in this study were PT. North Sumatra Regional Development Bank or commonly known as Bank SUMUT in 2019-2022. Bank Sumut is one of the banks in Indonesia which has the company name PT Regional Development Bank of North Sumatra, with its head office on Jl Imam Bonjol No. 18, Medan, North Sumatra.